Culture, conflict and cuisine : a quantitative assessment of terrestrial vertebrate off-take at the human-wildlife interface - Nieman, Wian Adriaan (Stellenbosch : Stellenbosch University, 2018)
Thesis (MScConsEcol)--Stellenbosch University, 2018.